Plato and the Pythagoreans - Szlezák, Thomas Alexander (Revista Archai, 2011)
Plato was not just a ´Socratic´. According to Diogenes Laertius, he started with Heraclitean philosophy before he met Socrates. His dialogues show that he was eager to take up other approaches as well. Next to the Eleatic influence, visible in the Parmenides and other late dialogues, Pythagorean philosophy seems to have had the strongest impact on his thinking. The biographical tradition asserts that he had repeatedly personal contact with the Pythagoreans from Tarentum, and Aristotle´s chapters 5 and 6 of Metphysics, Book I show that Plato´s philosophy of number and of the principles had great similarity to Pythagorean thinking. In this article, Aristotle´s statements about this part of Plato´s philosophy are examined one by one. It can be shown that in their entirety they form a coherent, meaningful whole.